2007
DOI: 10.1090/s0002-9947-07-04071-8
|View full text |Cite
|
Sign up to set email alerts
|

Compact operators and nest representations of limit algebras

Abstract: Abstract. In this paper we study the nest representations ρ : A −→ Alg N of a strongly maximal TAF algebra A, whose ranges contain non-zero compact operators. We introduce a particular class of such representations, the essential nest representations, and we show that their kernels coincide with the completely meet irreducible ideals. From this we deduce that there exist enough contractive nest representations, with non-zero compact operators in their range, to separate the points in A. Using nest representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In [25], it is shown that the fundamental relation for strongly maximal TAF algebras can be recovered from the (perhaps infinite dimensional) representation theory of such algebras. Since various TAF algebras (as well as our tensor algebras) are actually tensor algebras of correspondences, we expect that the completion of the classification scheme of Muhly and Solel [37] mentioned in the introduction will profit from a better understanding of their nest representations.…”
Section: Open Problems and Future Directionsmentioning
confidence: 99%
“…In [25], it is shown that the fundamental relation for strongly maximal TAF algebras can be recovered from the (perhaps infinite dimensional) representation theory of such algebras. Since various TAF algebras (as well as our tensor algebras) are actually tensor algebras of correspondences, we expect that the completion of the classification scheme of Muhly and Solel [37] mentioned in the introduction will profit from a better understanding of their nest representations.…”
Section: Open Problems and Future Directionsmentioning
confidence: 99%
“…The representation theory for non-selfadjoint operator algebras, although still in its infancy, is already playing an important role. Given a non-selfadjoint algebra, its nest representations are thought of as the proper generalization of the irreducible ones and a general theory around them is developing [26,6,21]. This paper contributes to the further development of that theory by analyzing such representations for algebras associated to directed graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Nest representations and their kernels were originally introduced by Lamoureux [29] as a generalization for primitive ideals. The second author, in joint work with Peters [25] and Kribs [22], applied the concept of a nest representation to the classification theory for non-selfadjoint operator algebras, including graph algebras [22] and limit algebras [25]. (See also [45].)…”
Section: Semicrossed Productsmentioning
confidence: 99%